Elämänlaatu ja iäkkäiden kaatumisten ehkäisy - Vaapio, Sari (fi=Turun yliopisto|en=University of Turku|, 2009)
Quality of life and fall prevention among the aged Improvement of quality of life is considered to be one of the most important goals of prevention, treatment and rehabilitation among the aged. The study aimed to describe and assess fall prevention interventions as a quality of life indicator, and to describe the social dimension of health-related quality of life among the aged. In addition, it aimed to assess the effects of fall prevention intervention on quality of life among the aged. The study was implemented by using a methodological triangulation. The data in the systematic review was retrieved from the databasis of medical and nursing sciences. Home-dwelling aged (n=19) participated in the qualitative study of a social dimension of quality of life. The data was gathered by the thematic interview method. The quantitative multifactorial fall prevention study comprised 591 participants, either the aged living at home or in sheltered housing, showing an increased risk of falling. Participants were randomized into an intervention or a control group. Follow-up measurements were carried out after a 12 month intervention. The data was collected by the 15D quality of life instrument and a structured questionnaire. Based on the systematic review, only in a few studies fall prevention produced positive effects on dimensions of quality of life (physical function, social function, vitality, mental health, environmental domain). Based on the thematic interview the social dimension of quality of life consisted of three themes: personal values, personal milieu and personal daily life. Based on the fall prevention program, depressive symptoms and distress decreased, managing in usual activities improved, sexual activity and phone contacts increased among men. In women, managing in usual activities improved, socializing increased and discomfort and symptoms decreased. Within the groups, self-perceived health improved among women in the intervention group and among men in the control groups. In addition, fear of falling and feelings of insecurity reduced among women in the intervention group. Personal daily life with its activities opened up new perspectives into the social dimension of good quality of life, which was emphasized especially in the interviews of the oldest participants. Multifactorial fall prevention can affect positively some physical and psychosocial dimensions of quality of life among the community-dwelling aged. Additional studies with larger sample sizes, longer follow-up periods and multiple outcome measures are needed. Fall prevention intervention may affect quality of life by different mechanisms, and the quantitative and qualitative assessment of its effects should also be included in the interventions of randomized controlled trials.

Elämänlaadun kohentuminen katsotaan yhdeksi tärkeimmistä ehkäisyn, hoidon ja kuntoutuksen päämääristä iäkkäiden keskuudessa. Tämän tutkimuksen tavoitteena oli kuvata ja arvioida elämänlaatu kaatumisten ehkäisytutkimusten vaikuttavuuden mittarina, kuvata iäkkäiden elämänlaadun sosiaalinen ulottuvuus ja arvioida kaatumisten ehkäisyn vaikutukset iäkkäiden elämänlaatuun. Tutkimuksessa käytettiin metodologista triangulaatiota. Systemaattisen kirjallisuuskatsauksen tiedot kerättiin lääke- ja hoitotieteellisistä tietokannoista. Kvalitatiiviseen elämänlaadun sosiaalisen ulottuvuuden tutkimukseen osallistui 19 kotona asuvaa iäkästä. Tiedot kerättiin teemahaastattelulla. Kvantitatiiviseen laaja-alaiseen kaatumisten ehkäisytutkimukseen osallistui 591 kotona tai palvelutalossa asuvaa iäkästä, joilla oli kohonnut kaatumisen vaara. Tutkittavat satunnaistettiin koe- tai vertailuryhmään, ja seurantamittaukset tehtiin 12 kuukautta kestäneen ehkäisyn jälkeen. Tiedot kerättiin terveyteen liittyvällä elämänlaatumittarilla 15D ja strukturoidulla kyselylomakkeella. Kirjallisuuskatsauksen perusteella kaatumisten ehkäisy tuotti positiivisia vaikutuksia elämänlaatuun vain muutamassa tutkimuksessa, joissa fyysinen ja sosiaalinen toimintakyky, energisyys, psyykkinen terveys sekä ympäristöllinen ulottuvuus parantuivat. Haastattelututkimuksen mukaan elämänlaadun sosiaalinen ulottuvuus muodostui kolmesta teemasta, joita olivat henkilökohtaiset arvot, oma lähiympäristö ja oma arki. Kaatumisten ehkäisyn vaikutuksesta miehillä masennusoireet ja ahdistuneisuus vähenivät ja tavanomaisista toiminnoista suoriutuminen, seksuaalinen aktiivisuus sekä puhelinkontaktit lisääntyivät. Naisilla tavanomaisista toiminnoista suoriutuminen ja vierailut lisääntyivät ja sekä vaivat että oireet vähenivät. Ryhmien sisäisiä muutoksia tarkasteltaessa koettu terveys parani koeryhmään kuuluvilla naisilla sekä koe- ja vertailuryhmään kuuluvilla miehillä. Lisäksi kaatumisen pelko ja turvattomuuden tunteet vähenivät koeryhmään kuuluvilla naisilla. Oman arjen sisältö ja siihen liittyvät toiminnot toivat erilaisen näkökulman hyvän elämänlaadun sosiaaliseen ulottuvuuteen, mikä korostui etenkin vanhimpien iäkkäiden haastatteluissa. Laajaalaisella ehkäisyohjelmalla voidaan vaikuttaa positiivisesti kotona asuvien iäkkäiden elämänlaadun joihinkin fyysisiin ja psykososiaalisiin ulottuvuuksiin. Tarvitaan lisää tutkimuksia, joissa on suuremmat otoskoot, pidemmät seuranta-ajat ja useampia vastemuuttujia. Kaatumisten ehkäisy voi vaikuttaa elämänlaatuun useilla eri mekanismeilla, ja sen vaikutusten arvioimisen tulisi sisältyä sekä määrällisesti että laadullisesti myös satunnaistettuihin, kontrolloituihin interventiotutkimuksiin.